Estudo da dinâmica e a modelagem de uma floresta semidecídua montana na região de Lavras-MG - Pulz, Frederico Aparecido (1998)
The approach of this study was centered around the study of the dynamics of a montane semideciduous forest and in the modeling of diametric structure of the forest. The basic data was obtained from the forest reserve of the Federal University of Lavras. The whole forest was divided into 126 plots with 400 m2 each. The evaluations were done in 1987, 1992 and 1996. In chapter 1, the growth in diameter, the mortality and the ingrowth of the species that compose the forest in question and in a particular way, the ecological groups that form the pioneer species, the light-demanding and shade-tolerant climax species was quantified; the dynamics of the forest from information obtained in three inventories, aiming to detect possible influences at the time of the modeling studies of diametric structure prognosis. Was interpreted in chapter 2, the performance of the prognosis method of forest structure based on the ratio of movement of the diameters was evaluated. In chapter 3, the performance of the prognosis model in which the variation of the diametric increment rate in individual trees or the Wahlenberg’s method are recognized. In chapter 4, the performance of the transition matrix was evaluated and compared to the methods presented in chapters 2 and 3. In all three chapters related to modeling, the influence of the changes occurred in the forest, starting from different evaluation periods, on the performance of the prognosis was also studied. During these evaluations, 136, 143 and 149 species were identified, considering the minimum measuring diameter equal to or above 5 cm. As main results, the following average alterations in the forest structure were detected: from the 149 existing species in the forest, only 6 presented frequency up to the diametric classes above 45 cm in diameter, which is the minimum diameter for use in sawmills; for the three periods studied, between 93 and 99% of the pioneer species, light-demanding climax and shade-tolerant climax, did not exceed the dimension of 25 cm of DBH; the periodic increment in diameter varied from 0.457 to 0.510 cm/year; the average forest mortality rate was 2.0% a year for the period 1987-1992, 3.6% a year for 1992-1996, and 2.3% a year for 1987-1996. The tree ingrowth rate in the measurement process varied from 2.2% to 2.7% a year for the three periods analyzed; for the ecological groups, the shade-tolerant climax species presented the highest ingrowth number (20.7 trees/ha/year) and the pioneers the lowest (3.3 trees/ha/year), in average for the three periods. The modeling of the stand diameter structure will only be efficient in all diametric classes if an efficient modeling of the ingrowth and mortality is achieved. The modeling of the stand diameter structure for the classes with diameter above 45 cm proved to be independent from the evaluation period. However, this modeling will be efficient if the prognosis period is not long, longer than 20 years. The transition matrix, ratio of diameter movement and Wahlenberg’s methods presented the same efficiency degree for forest structure prognosis as a whole. At the level of frequency by diametric class, these methods presented differenciated performance. The same fact was verified for the different evaluation periods. In this case, at least one of the methods was sensitive to changes in the forest structure.